Family Planning Vouchers in Low and Middle Income Countries: A Systematic Review. Issue 4 (17th November 2016) - Bellows, Ben; Bulaya, Carol; Inambwae, Sophie; Lissner, Craig L.; Ali, Moazzam; Bajracharya, Ashish
Abstract : Family planning (FP) vouchers have targeted subsidies to disadvantaged populations for quality reproductive health services since the 1960s. To summarize the effect of FP voucher programs in low‐ and middle‐income countries, a systematic review was conducted, screening studies from 33 databases through three phases: keyword search, title and abstract review, and full text review. Sixteen articles were selected including randomized control trials, controlled before‐and‐after, interrupted time series analyses, cohort, and before‐and‐after studies. Twenty‐three study outcomes were clustered around contraceptive uptake, with study outcomes including fertility in the early studies and equity and discontinuation in more recent publications. Research gaps include measures of FP quality, unintended outcomes, clients' qualitative experiences, FP voucher integration with health systems, and issues related to scale‐up of the voucher approach.